Potential and Obstacles in Cultural Heritage Development in Tanjungpinang City - Nika Purnamasari; Zikri Raudhatul Ahsan; Ari Ridho Susanto; Bayu Saputra; Sri Wahyuni (Jurnal Pengabdian Masyarakat Bestari, 2023)
The city of Rebah is a place for tourists to visit. In the city of Rebah, there are several relics such as tombs, collapsed buildings, docks. The city of Rebah has an area of ​​4 hectares, has good views, the view from the pier directly shows the Carang river bridge and there are mangrove trees. In this research the author used qualitative methods. According to Bogdan and Taylor (1975:5) defines that "qualitative methods" are research procedures that produce descriptive data. In the potential that exists in the city of Rebah, there are several obstacles. The aim of this research is to determine the potential and obstacles in historical tourist attractions in the city of Rebah. The results of this research show that the city of Rebah has the potential to develop sports in the form of rock climbing, suspension bridges and restaurants. Apart from that, there are obstacles in the city of Rebah, the need for additional caretakers, lack of funds for the development of the city of Rebah, damage to supporting facilities such as toilets and lactation rooms.